Ontogenetic development and redescription of Eotetranychus kankitus (Acariformes: Tetranychidae) - Li, Juan; Guo, Jian-Jun; Jin, Dao-Chao (Zootaxa, 2018)
Eotetranychus kankitus Ehara, 1955 is redescribed from females, males, deutonymphs, protonymphs and larvae collected on Citrus reticulata Blanco (Rutaceae) from China. The ontogenetic changes in leg chaetotaxy are provided and compared with the similar species Eotetranychus tiliarium (Hermann, 1804) and the considerably hypotrichous species Eotetranychus xuzhouensis (Wang & Ma, 1987).